Le secret professionnel au Québec : une hydre à trente-neuf têtes rôde dans le droit de la preuve - Morissette, Yves-Marie; Shuman, Daniel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
Under Quebec law, the members of thirty-nine regulated professions are bound by statute to professional secrecy. This obligation is reinforced by section 9 of the Quebec Charter of Human Rights and Freedoms. It protects patients and clients against the extrajudicial disclosure of confidential information but it also operates as an evidentiary privilege which the courts must enforce ex officio in all proceedings of a non-criminal nature. According to the authors, this statutory equation of professional confidentiality with privilege necessarily leads to the overgrowth of privilege or to the atrophy of confidentiality. The rule interferes excessively with the administration of civil justice and compels the courts to adopt result-oriented interpretations detrimental to the coherence of the law. The article first describes the relationship between the applicable legislation and the several codes of professional ethics defining the scope of professional secret. A second part explores the possible justifications for legal duties of confidentiality and evidentiary privileges ; most of these rationales are compatibles with a distinction between in-court and out-of-court requirements of secrecy. The authors then review in a third part various cases in which Quebec courts have dealt with objections based on professional secret. Three conflicting interpretations were adopted in these cases. All three interpretations restrict the scope of professional privilege, sometimes at the expense of legitimate claims for out-of-court confidentiality. It therefore appears desirable to re-establish in the legislation a distinction between the judicial and extrajudicial aspects of professional secret. The conclusion contains suggestions for a reform of the law of professional secret in Quebec.